Bioremediation Of Arsenic By Bacteria Isolatedfrom Arsenic Contaminated Marine Environment Of Goa Harbour Of India - NEELAM SINGH (International Journal of Pharma and Bio Sciences, 2011)
Biological characterization and bioremediation potential of an arsenic hyper-accumulating marine mesophilic bacterium, Aeromonas punctata strain MPT4 isolated from the Ferromanganese ore loading site of marmugao port trust harbour (N15°24’ 28.3” and E 073° 48’ 17.6”), Goa, India is presented in this study. The taxonomic placement of this isolate was done on the basis of biochemical tests(as per Bergey’s Manual), FAME analysis and 16s rDNA sequencing. MIC of sodium arsenate and arsenite were determined in Mineral salts medium supplemented with 0.4% glucose and increasing concentrations of sodium arsenate and arsenite separately. Growth behaviour of this isolate reveals that it can tolerate well upto 150 mM sodium arsenate. Intracellular arsenic content of bacterial cells was estimated by HG-AAS. Significantly high levels of arsenate was found in the cell free extracts of sonicated cells, after washing the arsenate grown cells twice with 50mM Tris-Cl buffer. Interestingly, PCR analysis of genomic DNA and plasmid DNA using arsC specific primers revealed the absence of arsenate reductase gene. These findings clearly suggest that although Aeromonas punctata MPT4 is devoid of arsC gene, it hyperacumulates arsenic (arsenate) and may be successfully used for bioremediation of arsenate contaminated marine environment.